Divergence of metabolites in three phylogenetically close Monascus species (M. pilosus, M. ruber, and M. purpureus) based on secondary metabolite biosynthetic gene clusters - Higa, Yuki (BMC Genomics, 2020)
BACKGROUND: Species of the genus Monascus are considered to be economically important and have been widely used in the production of yellow and red food colorants. In particular, three Monascus species, namely, M. pilosus, M. purpureus, and M. ruber, are used for food fermentation in the cuisine of East Asian countries such as China, Japan, and Korea. These species have also been utilized in the production of various kinds of natural pigments. However, there is a paucity of information on the genomes and secondary metabolites of these strains. Here, we report the genomic analysis and secondary metabolites produced by M. pilosus NBRC4520, M. purpureus NBRC4478 and M. ruber NBRC4483, which are NBRC standard strains. We believe that this report will lead to a better understanding of red yeast rice food. RESULTS: We examined the diversity of secondary metabolite production in three Monascus species (M. pilosus, M. purpureus, and M. ruber) at both the metabolome level by LCMS analysis and at the genome level. Specifically, M. pilosus NBRC4520, M. purpureus NBRC4478 and M. ruber NBRC4483 strains were used in this study. Illumina MiSeq 300 bp paired-end sequencing generated 17 million high-quality short reads in each species, corresponding to 200 times the genome size. We measured the pigments and their related metabolites using LCMS analysis. The colors in the liquid media corresponding to the pigments and their related metabolites produced by the three species were very different from each other. The gene clusters for secondary metabolite biosynthesis of the three Monascus species also diverged, confirming that M. pilosus and M. purpureus are chemotaxonomically different. M. ruber has similar biosynthetic and secondary metabolite gene clusters to M. pilosus. The comparison of secondary metabolites produced also revealed divergence in the three species. CONCLUSIONS: Our findings are important for improving the utilization of Monascus species in the food industry and industrial field. However, in view of food safety, we need to determine if the toxins produced by some Monascus strains exist in the genome or in the metabolome.